Factors Associated with One-Year Outcome after Distal Radial Fracture Treatment. (April 2015) - Cowie, Jonathan; Anakwe, Raymond; McQueen, Margaret
Purpose: To identify factors that affect functional outcome one year after distal radial fracture treatment. Methods: 521 women and 121 men aged 16 to 92 (mean, 59) years with distal radial fractures underwent external fixation (n=123), open reduction and internal fixation (n=63), a combination of both (n=10), distal radial osteotomy for symptomatic malunion (n=90), or casting with (n=194) or without (n=162) prior closed manipulation under regional anaesthesia. The indication for surgery (rather than casting) was metaphyseal instability. Radiographic evaluation (dorsal angulation, radial shortening, carpal malalignment, and malunion) was made before and after treatment and after fracture healing. Functional evaluation (range of movement, grip strength, and activities of daily living) was made at a mean of 16 (range, 6–54) months after injury. Results: After multiple regression analysis, poorer functional score was associated with increasing age (p<0.001), dorsal angulation after healing (p<0.016), presence of volar comminution (p=0.005), and pain (p<0.001). Poorer grip strength was associated with non-dominant side injury, increasing age, dorsal angulation after healing, positive ulnar variance, comminution, and pain (all p<0.001). Predicted malunion showed colinearity with age ( r =0.657), dorsal comminution ( r =0.694), and dorsal angulation ( r =0.626). Conclusion: Understanding factors associated with outcome helps surgeons to make the treatment decision for distal radial fracture to achieve optimum outcome.